Jenner of George Street the story of Frank Jenner, Sydney's soulwinning sailor - Wilson, Raymond Ernest, 1942- (Hurstville, NSW Dr Raymond Ernest Wilson, 2000)
Includes bibliographical references.
Brethren writer.
Keywords: Jenner, Frank Arthur, -- 1903-1977; Australia -- Church history -- 20th century; Brethren movement -- biography -- 20th century -- Australia